DIGITALIZATION OF THE BLUE ECONOMY: CONCEPTUAL PAPER FOR THE DEVELOPMENT OF THE GLOBAL HALAL HUB IN INDONESIA - Annisa, Arna Asna; Indriyani, Fany (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
Economic growth that has not yet fully recovered due to COVID-19 requires creative economic policies that can elevate public sectors that have not been a priority. On the other hand, digital technology is recognized as a breakthrough in upgrading progress in various aspects. This conceptual paper aims to synthesize the role of digital technology in developing the halal industry through the use of the blue economy in the form of a global halal hub policy in Indonesia. This research was conducted in a structured and systematic descriptive manner. A study of various Scopus articles found that supply chain traceability in the halal industry requires a guarantee of halal product guarantees from upstream to consumers. Facing high global halal growth, it is necessary to synergize the role of land, sea, and air logistics with information technology and economic digitization systems. Through the development of digitalization of the blue economy, the Indonesian global halal hub can be an alternative to improving logistics routes for halal products in international trade with guaranteed supply chains that are controlled through information technology systems so that information openness between agents will emerge and can automatically accelerate domestic and international economic growth. The novelty of this research is that it synergizes the potential of the blue economy sector, which has not been studied much for the development of the halal industry at the global level. This can be a reference so that the involvement of the blue economy role is also prioritized in making halal logistics policies.